2020
DOI: 10.1123/ijspp.2019-0643
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Implementation of the Athlete Biological Passport and Female Elite Runners’ Performance

Abstract: The purpose of this research was to evaluate the performances of female middle- and long-distance runners before and after the implementation of a new antidoping strategy (the Athlete Biological Passport [ABP]) in a country accused of systematic doping. A retrospective analysis of the results of Russian National Championships from 2008 to 2017 was performed. The 8 best female performances for the 800-m, 1500-m, 3000-m steeplechase, 5000-m, and 10,000-m events from the semifinals and finals were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The data used for analyses consisted of the performance records and sanction status of male weightlifters from all international competitions, which were obtained from the IWF website. While prior analyses have been conducted using performance data in the different disciplines of athletics [11,12], this study aimed to facilitate the development of a more scientific and systematic anti-doping program that aligns with the international standards supported by prior studies that analyzed running performance. We pooled athletic performance and sanction status from male weightlifters to conduct comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The data used for analyses consisted of the performance records and sanction status of male weightlifters from all international competitions, which were obtained from the IWF website. While prior analyses have been conducted using performance data in the different disciplines of athletics [11,12], this study aimed to facilitate the development of a more scientific and systematic anti-doping program that aligns with the international standards supported by prior studies that analyzed running performance. We pooled athletic performance and sanction status from male weightlifters to conduct comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…178 The observed decrease in athletes' variability in reticulocyte percentage (%RET) since 2009 has also been attributed to the ABP, and its deterrent effect has been mentioned as key reason for the significant decline in athletic performance assessed for female middle-and long-distance runners before and after the implementation of this anti-doping strategy. 179 Conversely, the hypothesized significant decline in the estimated prevalence of blood doping in elite track and field athletes was not confirmed in a study that employed seven hematological parameters constituting the abnormal blood profile score (ABPS), determined for a total of 3,683 blood samples collected at two major sporting events in 2011 and 2013. Between 2011 and 2013, the estimated prevalence of blood doping in elite track and field athletes was 18% and 15%, which was not found to be statistically significant.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 98%
“…The hematological module of the ABP, which visualizes fluctuations in selected biological markers collated over an athletes sporting career, was installed in 2009 and has since demonstrated its capability of detecting blood doping practices 178 . The observed decrease in athletes' variability in reticulocyte percentage (%RET) since 2009 has also been attributed to the ABP, and its deterrent effect has been mentioned as key reason for the significant decline in athletic performance assessed for female middle‐ and long‐distance runners before and after the implementation of this anti‐doping strategy 179 . Conversely, the hypothesized significant decline in the estimated prevalence of blood doping in elite track and field athletes was not confirmed in a study that employed seven hematological parameters constituting the abnormal blood profile score (ABPS), determined for a total of 3,683 blood samples collected at two major sporting events in 2011 and 2013.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…For example, it was demonstrated that the introduction of the blood module of the ABP negatively affected performance results in middle‐ and long‐distance runners of a country that was accused of large‐scale doping use. The decrease of performance results in this population was accompanied by a large number of cases (incidents) of doping as the ABP was introduced 20 …”
Section: Introductionmentioning
confidence: 99%